Terapan Analisis Fundamental atau Teknikal Dalam Penilaian Saham (Kajian Pada Perusahaan Food And Beverage yang Listed di BEI Periode 2017-2019) - Baiq Desthania Prathama (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to choose an analysis of stock investment decisions on the IDX. The research design is an associative research that is equipped with an in-depth description of the stock price model produced in this study. Observation data is in the form of panel data, namely 2017-2020 and 21 food and beverage companies listed on the IDX. The fundamental model [stock price=f(NPM, ROI and ROE) was built with 84 observational data, while the model with the explanatory factor was technical (stock price(t-1)) , including when initially entering the EPS variable using 63 observational data. The findings show that the stock price model with an explanatory variable in the form of fundamental factors cannot be used as a decision-making tool, because the independent variables are highly correlated (the implication is that the t-test with Ha criteria is accepted, but in the F-test the criteria H0 is accepted). The final model produced is an explanatory factor in the form of stock price (t-1) to stock price (stock price = f(share price (t-1), where stock price can be explained at the level of 68.60%. This study confirms for investors stocks that lead to professionals to explore the various theories that exist in technical analysis